Проблеми неонатального скринінгу на вроджену гіперплазію кори надниркових залоз - Зелінська, Н. Б.; Погадаєва, Н. Л.; Глоба, Є. В.; Ніфонтова, Л. В.; Орлова, Т. О. (Clinical Endocrinology and Endocrine Surgery, 2013)
The article presents a review of literature for the last 35 years about the problems of diagnostic and treatment of various forms of adrenal dysfunction in preterm and term infants before and with the beginning of neonatal screening on congenital adrenal hyperplasia (CAH). The factors affecting the main diagnostic marker of CAH 17-hydroxyprogesterone (17-OHP) are presented. The reasons that lead to false-positive and false-negative indicators 17-OPH during the screening of newborns and in early childhood are analyzed. The ways of improving the predictive value and sensitivity of the neonatal screening of CAH are reported.